To Add or Not to Add: Would the Addition of Dalbavancin to Formulary Decrease Admissions for Acute Bacterial Skin and Skin Structure Infections (ABSSSI)?. (4th October 2017) - Freshwater, Dustin; Murphy, Nina; Hecker, Michelle T
Abstract: Background: One of the major advantages of dalbavancin is that it may be administered as a single dose for the treatment of acute bacterial skin and skin structure infections (ABSSSI). Our objective was to determine the number (%) of patients with an ABSSSI diagnosis whose admission to a county hospital could have been avoided if dalbavancin was on formulary. Methods: From November 2016 to April 2017, we reviewed encounters for adult patients seen in the emergency department or inpatient setting with a primary ABSSSI diagnosis. For those admitted, potential candidates for dalbavancin included those with ≥2 local signs/symptoms of ABSSSI AND ≥1 systemic sign of infection AND none of the exclusion criteria used in the DISCOVER 1 and 2 trials. Potential candidates were classified as qualifying for dalbavancin if they received IV antibiotics for ≥3 days but <14 days, had no Gram-negative or anaerobic organisms isolated, had no operative intervention nor ≥2 incision and drainage procedures, had a contraindication to linezolid, and did not require hospitalization for management of other comorbidities. Results: Of 1203 patients with a primary diagnosis of ABSSSI, only 219 (18%) were admitted, of whom only 11 (5%) were classified as potential candidates for dalbavancin. The most common reasons admitted patients were excluded as potential candidates were not meeting signs and symptoms criteria ( n = 147), age <18 years ( n = 13), being admitted to the hospital for >14 days ( n = 11), periorbital or joint cellulitis ( n = 9), deep seated infection ( n = 5), required admission for another reason ( n = 5), and diabetic foot ulcer ( n = 4). Of the 11 potential candidates, one qualified for dalbavancin based on our criteria. Conclusion: At our hospital only a minority of patients with a primary diagnosis of ABSSSI were admitted and one ultimately met our criteria for dalbavancin use. Adding dalbavancin to our formulary would not have resulted in fewer admissions for patients with ABSSSI. Disclosures: All authors: No reported disclosures.